The COVID-19 Pandemic in Latin American and Caribbean Countries: The Labor Supply Impact by Gender - Mariana Viollaz; Mauricio Salazar-Saenz; Luca Flabbi; Monserrat Bustelo; Mariano Bosch (Institute of Labor Economics (IZA), 2022)
We study the labor supply impact of the COVID-19 pandemic by gender in four Latin American and Caribbean (LAC) countries: Brazil, Chile, Dominican Republic, and Mexico. To identify the impact, we compare labor market stocks and labor market flows over four quarters for a set of balanced panel samples of comparable workers before and after the pandemic. We find that the pandemic has negatively affected the labor market status of both men and women, but that the effect is significantly stronger for women, magnifying the already large gender gaps that characterize LAC countries. The main channel through which this stronger impact is taking place is the increase in child care work affecting women with school-age children.
Keywords: J6; J16; J46; O10; O17; 330; labor supply; labor market transitions; COVID-19; gender differentials; Latin American and Caribbean countries